2018
DOI: 10.7600/jpfsm.7.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated eccentric contractions with different loads on blood circulation and collagen fiber orientation in the human Achilles tendon

Abstract: The purpose of this study was to compare changes in blood circulation and collagen fiber orientation in the Achilles tendons after repeated eccentric contractions (ECC) with different loads. Thirteen healthy male subjects performed two ECC protocols with different loads and then remained relaxed for 40 min after ECC. Each leg was randomly allocated to low-load protocol (180 repetitions at 50% of one repetition maximum [1RM]) and high-load protocol (75 repetitions at 120% of 1RM). Before and after ECC, blood vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Accordingly, it might be considered that the hamstring can work more eccentrically at a more muscle-lengthened position during the SLDL; as a result, Golgi tendon organs were enhanced and inhibited hamstring contraction, and the muscles became more flexible. In addition, the previous study reported that eccentric quadriceps exercise decreases the patellar tendon stiffness17 ) and eccentric triceps surae exercise improves the collagen fiber orientation of Achilles tendon18 ) . Accordingly, increase in flexibility following low-intensity eccentric hamstring exercise might be due to these changes of the tendon property.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it might be considered that the hamstring can work more eccentrically at a more muscle-lengthened position during the SLDL; as a result, Golgi tendon organs were enhanced and inhibited hamstring contraction, and the muscles became more flexible. In addition, the previous study reported that eccentric quadriceps exercise decreases the patellar tendon stiffness17 ) and eccentric triceps surae exercise improves the collagen fiber orientation of Achilles tendon18 ) . Accordingly, increase in flexibility following low-intensity eccentric hamstring exercise might be due to these changes of the tendon property.…”
Section: Discussionmentioning
confidence: 99%